2013
DOI: 10.1111/cen.12099
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance does not affect early embryo development but lowers implantation rate in in vitro maturation–in vitro fertilization–embryo transfer cycle

Abstract: Pregnancy rate after IVM is impaired in IR patients with PCOS. Oocyte development and embryo quality are not affected, suggesting that the effects of hyperinsulinemia on endometrial function and implantation process underlie the decreased pregnancy rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 44 publications
2
40
0
1
Order By: Relevance
“…Interestingly, embryo development was not affected in patients with insulin resistance, indicating that, in fact, insulin-resistant patients with PCOS have impaired endometrial receptivity. 58 The pathophysiology behind insulin resistance is complex. Most authors believe that, in obese patients, insulin resistance is determined by liver accumulation of free fatty acids (FFAs) released by visceral fat.…”
Section: Hyperinsulinemiamentioning
confidence: 99%
“…Interestingly, embryo development was not affected in patients with insulin resistance, indicating that, in fact, insulin-resistant patients with PCOS have impaired endometrial receptivity. 58 The pathophysiology behind insulin resistance is complex. Most authors believe that, in obese patients, insulin resistance is determined by liver accumulation of free fatty acids (FFAs) released by visceral fat.…”
Section: Hyperinsulinemiamentioning
confidence: 99%
“…For example, in patients with polycystic ovary syndrome, higher IR altered the implantation rate after in-vitro fertilization. 30 Similarly, Paretti et al 31 demonstrated that preeclampsia can be predicted by simple insulin sensitivity indexes measured independently in both early and late pregnancy. Hauth et al 32 confirmed these findings in a large cohort of patients tested between the 22nd and 26th weeks of gestation.…”
Section: Resultsmentioning
confidence: 98%
“…Blood pressures, waist circumference, and body mass index were measured as described by Ryu and colleagues [24]. The level of serum gonadotropins and other hormones were measured as described previously [26]. …”
Section: Methodsmentioning
confidence: 99%